2006
DOI: 10.1111/j.1365-2621.2006.01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of different Teucrium montanum L. Extracts

Abstract: The sequential extraction of Teucrium montanum L. was realised with five solvents of different polarities (70% methanol, petroleum ether, chloroform, ethyl acetate, and n-butanol) and HPLC method was used for identification of phenolic compounds. The total phenolic content of the extracts was determined spectrophotometrically according to the Folin-Ciocalteau procedure and range from 0 to 296 mg g )1 .The antioxidant activity of extracts was tested by measuring their ability to scavenge reactive hydroxyl radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…In the present study, the phenolic contents of the ethanol extracts of N. cadmea were identified using the HPLC method and these are listed in Table . Some phenolic compounds determined in the present study, such as ferrulic, gallic, caffeic, vanilic, chlorogenic, ellagic acids, and rutin, were obtained from Lamiaceae plants in previous studies (Canadanovic‐Brunet et al., ; Mamadalieva et al., ; Roby et al., ). In addition, of these phenolic contents, ellagic acid is well known as an antioxidant (Mertens‐Talcott, Talcott, & Percival, ).…”
Section: Resultsmentioning
confidence: 82%
“…In the present study, the phenolic contents of the ethanol extracts of N. cadmea were identified using the HPLC method and these are listed in Table . Some phenolic compounds determined in the present study, such as ferrulic, gallic, caffeic, vanilic, chlorogenic, ellagic acids, and rutin, were obtained from Lamiaceae plants in previous studies (Canadanovic‐Brunet et al., ; Mamadalieva et al., ; Roby et al., ). In addition, of these phenolic contents, ellagic acid is well known as an antioxidant (Mertens‐Talcott, Talcott, & Percival, ).…”
Section: Resultsmentioning
confidence: 82%
“…This is in accordance with the polarity of the solvent used for the extraction and the solubility of phenolic compounds present in the extract. 41 For samples assayed for the presence of anthocyanins, the ionization state can be important when assessing the antioxidant activity. 22 For instance, the quinoidal pseudo-base and base of malvidin-3-glucoside generated at pH 4.0 and 7.0, respectively, exhibit differences in antioxidant activity.…”
Section: Ramos-escudero Et Almentioning
confidence: 99%
“…Significant differences have been reported for TPC among the verities. Jasna et al [15] has found TPC in the range of 2.51-3.5 mg\g for bran extracts. Moreover Sathe et al [2] has determined differences in TPC extracted in various solvents with highest antioxidant activity for the n-butanol extract of almond skin T. while the lowest antioxidant activity for methanol extract.…”
Section: Resultsmentioning
confidence: 96%